Improving the Eighth Grade Students' Simple Present Tense Mastery by Using Stick Figures at SMP Negeri 5 Jember in the 2016/2017 Academic Year - Mariska Aryaningtyas; Siti Sundari; Zakiyah Tasnim (FKIP e-PROCEEDING, 2017)
Abstract: The aims of this research were: (1) to improve the eighth grade students’ active participation in the teaching learning process of Simple Present Tense by using stick figures at SMP Negeri 5 Jember in the 2016/2017 academic year, and (2) to improve the eighth grade students’ Simple Present Tense mastery by using stick figures at SMP Negeri 5 Jember in the 2016/2017 academic year. The design of the research was Classroom Action Research (CAR). The research area was chosen by using the Purposive Method. The research subjects were the Eighth Grade Students of VIIIC at SMP Negeri 5 Jember in the 2016/2017 academic year. The data collection methods were obtained from administering a tense test, observation, giving interview, and documentation. The research was done in 2 cycles to achieve the criteria of success. Based on the results of the research, it showed improvement at the students’ active participation and their tense mastery. The percentage of the students’ active participation increased from 42% (16 students) in cycle 1 to 79% ( 30 students) in meeting 1 of cycle 2 and 87% (33 students) in meeting 2 of Cycle 2. Then, the percentage of the students who got ≥75 in the tense test increased from 57% (21 students) in cycle 1 to 81% (29 students) in cycle 2. It indicated that the results of the research met the criteria of success that stick figures could improve the eighth grade students’ active participation and Simple Present Tense Mastery. Keywords: Stick Figures, Students' Active Participation, Simple Present Tense Master